Philippine Agriculture under the World Trade Organization, 1995-2005: Gains, Losses, and Prospects - Bernabe, Maria Dolores; Quinsaat, Sharon M. (Kasarinlan: Philippine Journal of Third World Studies; Vol 24 No 1-2 (2009): The Philippines in the WTO, 2011)
The paper reviews the Philippines’s implementation of the Agreement on Agriculture (AoA) and the agricultural sector’s performance in the World Trade Organization (WTO) from 1995 to 2005. It posits that the forecasted benefits from the implementation of the AoA were based on a host of faulty assumptions. The continued proliferation of trade distorting domestic subsidies in developed countries, the use of tariff peaks and other forms of nontariff barriers, and the Philippine government’s failure to deliver the necessary safety nets to small farmers and agricultural producers undermined the country’s capability to gain from liberalized trade under the WTO. The paper also examines the evolution of the Philippines’s position on the AoA as the country became an active member of developing-country formations in the WTO, such as the G20 and the G33. The paper underscores the importance of a comprehensive strategy in trade negotiations—one that links productivity and competitiveness enhancement programs to trade liberalization commitments and harmonizes negotiating agenda across multilateral, regional, and bilateral trade agreements.
Keywords: World Trade Organization · Agreement on Agriculture · Philippines · General Agreement on Tariffs and Trade · Uruguay Round agreements · G20 · G33